Absorption Coefficient of Bulk III-V Semiconductor Materials: A Review on Methods, Properties and Future Prospects - Lee H.J.; Gamel M.M.A.; Ker P.J.; Jamaludin M.Z.; Wong Y.H.; David J.P.R. (Springer, 2023)
Crystal structure; Energy gap; Genetic algorithms; III-V semiconductors; Optical properties; Solar power generation; Structural design; Absorption coefficients; Bulk growth; Bulk III-V semiconductors; Bulk semiconductors; Comparatives studies; Future prospects; Property; Quaternary; Semiconductor crystals; Ternary; Infrared devices